Assessing the Impact of Corporate Entrepreneurship in the Financial Performance of Subsidiaries of Colombian Business Groups: under Environmental Dynamism Moderation - Rodríguez Peña, Antonio (Pontificia Universidad Católica del Perú, 2021)
Corporate entrepreneurship creates opportunities in employment, technological advances, value creation and cultural transformation for entrepreneurial ecosystems, entrepreneurs, governments, economies and societies around the globe. The purpose of this study was to assess the impact of corporate entrepreneurship on the financial performance of subsidiaries in Colombian business groups under the moderating effect of the environmental dynamism, since the relationship between these two in emerging economies differs from developed economies. Using a cross-sectional Structural Equation Modeling analysis, this study assessed the impact of entrepreneurial orientation and corporate venturing on the financial performance of 87 subsidiaries of Colombian business groups at different levels of environmental dynamism. This study also confirmed that the relationship between corporate entrepreneurship and performance is context-dependent, and that entrepreneurial orientation has a strong and positive causal relationship with corporate venturing. Additionally, it was observed that subsidiaries of Colombian business groups increase their financial performance when the entrepreneurial orientation does; and decrease the same when corporate venturing does. Furthermore, the results show that environmental dynamism does not have a moderating effect on the relationship between corporate entrepreneurship of subsidiaries in Colombian business groups and their performance. This dissertation would contribute to important areas in Latin American businesses, where such studies are scarce.

El emprendimiento corporativo crea oportunidades de empleo, avances tecnológicos, creación de valor y transformación cultural para los ecosistemas empresariales, los empresarios, los gobiernos, las economías y las sociedades de todo el mundo. El propósito de este estudio fue evaluar el impacto del emprendimiento corporativo en el desempeño financiero de las filiales de los grupos empresariales colombianos bajo el efecto moderador del dinamismo del ambiente de negocios, ya que la relación entre estos dos en las economías emergentes difiere de las economías desarrolladas. Utilizando un análisis transversal de Modelado de Ecuaciones Estructurales, este estudio evaluó el impacto de la orientación hacia el emprendimiento y el corporate venturing sobre el desempeño financiero de 87 subsidiarias de grupos empresariales colombianos en diferentes niveles de dinamismo del ambiente de negocios. Este estudio también confirmó que la relación entre el emprendimiento corporativo y el rendimiento depende del contexto, y que la orientación hacia el emprendimiento tiene una relación causal fuerte y positiva con el corporate venturing. Además, se observó que las filiales de los grupos empresariales colombianos aumentan su rendimiento financiero cuando lo hace la orientación hacia el emprendimiento; y disminuyen el mismo cuando lo hace el corporate venturing. Además, los resultados muestran que el dinamismo del ambiente de negocios no tiene un efecto moderador en la relación entre el emprendimiento corporativo de las filiales de los grupos empresariales colombianos y su desempeño. Esta disertación contribuye a áreas importantes en las empresas latinoamericanas, donde estos estudios son escasos.
Keywords: Emprendimiento (Administración); Empresas--Colombia; Empresas--Aspectos financieros; http://purl.org/pe-repo/ocde/ford#5.02.04